Individual Investors Psychology and Investment Decision in NEPSE - Gyanwali, Inju; Neupane, Geeta (The Lumbini Journal of Business and Economics, 2021)
This study attempts to examine individual investor’s psychology and their investment decision in NEPSE with an objective to identify whether the individual psychological factors and their biases influence decision making in Nepalese stock market. The sample size of 347 was taken from broker office located in Butwal city for this study. Psychological factors named anchoring, herding, mental accounting, overconfidence; regret aversion and loss aversion were undertaken. These factors were further categorized as cognitive bias (anchoring, herding and mental accounting) and emotional bias (overconfidence, regret aversion and loss aversion). Self-administered questionnaire were used to collect data. In the same way descriptive and analytical research design were used to analyze the data. Multiple regression analysis showed that overconfidence, herding and loss aversion have impact on investment decision whereas anchoring, mental accounting and regret aversion does not have an impact on individual investors investment decision. The result further showed that cognitive and emotion biases both have positive and significant influence on the investment decision making of individual investor in Nepalese stock exchange.